Decreased dicamba transport due to increased flavonoid biosynthesis: a candidate dicamba resistance mechanism - Pettinga, Dean J., author; Gaines, Todd A., advisor; Ward, Sarah, committee member; Sloan, Daniel, committee member (Colorado State University. Libraries, 2016)
Resistance to dicamba (a synthetic auxin herbicide) has been documented in Kochia scoparia (L.) Schrad. populations since 1994, but the molecular mechanisms of observed resistance cases remain elusive. An RNA-Seq approach was used to identify transcripts with significantly differential transcription responses between inbred lines of dicamba-resistant (9425R) and dicamba-susceptible (7710S) K. scoparia in response to dicamba application. Among the significantly differentially expressed transcripts was both Chalcone Synthase (CHS), the first enzyme and rate-limiting step in the flavonoid biosynthesis pathway, and Flavono 3'-Hydroxylase (F3'H), which catalyzes the conversion of quercetin into kaempferol, known inhibitors of auxin transport. In silico expression patterns of both transcripts were confirmed with qRT-PCR. An F2 population derived from a cross of 9425R x 7710S segregating for the resistance phenotype was assayed for CHS and F3'H expression using qRT-PCR. Dicamba-resistant F2 individuals displayed significantly higher CHS transcript abundance compared to dicamba-susceptible F2 individuals, associating the resistance phenotype of 9425R with a greater overall flux through the flavonoid biosynthesis pathway. Increased production of the auxin transport inhibitors quercetin and kaempferol could reduce intercellular transport and vascular loading of dicamba, causing a substantial reduction in dicamba efficacy by reducing its translocation to sensitive meristematic tissue, thereby conferring the observed resistance phenotype.
Keywords: chalcone synthase; flavonoids; resistance; dicamba; auxin; kochia